Recurrence and local lymphogenic metastasis of conjunctival melanoma - A. M. Andreychenko; T. A. Mozhaeva (Опухоли головы и шеи)
Objective. Study of local lymphogenic metastasis (inside the conjunctiva) of conjunctival melanoma.Introduction. Conjunctiva is a transparent mucous membrane with a large number of blood vessels. Normally, it contains melanocytes which explains possibility of development of pigmented tumors in the conjunctiva. Conjunctival melanoma is a rare tumor:it constitutes about 1–3 % of all malignant tumors of the ocular adnexa, and according to different authors its incidence rate is 0.02–0.08 for 100 thousand people. Melanoma is characterized by frequent recurrences and hematogenic and lymphogenic metastases.Materials and methods. Fifteen (15) patients with conjunctival melanoma were included in the study. Tumor recurrence and/or tumor seeding were reasons for inclusion in the study. For graphic representation of tumor localization, we developed a diagram of the conjunctival surface which subsequently was improved using a diagram of lymphatic vessels of the bulbar conjunctiva. An interpretive map of the conjunctival surface produced this way was taking into account lymph node structure of the bulbar conjunctiva.Results and discussion. Recurrence was observed only in 4 of 15 patients. Seedings were usually localized in neighboring or distant areas in respect to the primary lesion localization, which, supposedly, can be explained by the structure of conjunctival lymphatic system.Conclusion. In one third of the cases (in 5 of 15 patients) primary tumors were localized near large lymphatic vessels. Moreover, in all cases seeding was observed near the same lymphatic collectors, but at a distance from the primary lesion localization. This confirms possibility of local metastasis through conjunctival lymphatic paths.